2020
DOI: 10.3390/ijms21041404
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Rescue of Dyrk1A Overexpression Alterations in Mice with Fontup® Dietary Supplement: Role of Green Tea Catechins

Abstract: Epigallocatechin gallate (EGCG) is an inhibitor of DYRK1A, a serine/threonine kinase considered to be a major contributor of cognitive dysfunctions in Down syndrome (DS). Two clinical trials in adult patients with DS have shown the safety and efficacy to improve cognitive phenotypes using commercial green tea extract containing EGCG (45% content). In the present study, we performed a preclinical study using FontUp®, a new nutritional supplement with a chocolate taste specifically formulated for the nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 53 publications
(81 reference statements)
1
23
2
1
Order By: Relevance
“…EGCG exerts broad effects on several nonneuronal targets, including myelination (57) and microbiota (58). Several studies have demonstrated that EGCG crosses the blood-brain barrier in rodents after oral administration (59)(60)(61), including in TgDyrk1A transgenic mice, another genetic model of Down syndrome (62). In fact, EGCG has been detected in rat frontal cortex and hippocampus (60), so the effects observed in our study could be, indeed, mediated by direct action of EGCG on these structures.…”
Section: Discussionsupporting
confidence: 56%
“…EGCG exerts broad effects on several nonneuronal targets, including myelination (57) and microbiota (58). Several studies have demonstrated that EGCG crosses the blood-brain barrier in rodents after oral administration (59)(60)(61), including in TgDyrk1A transgenic mice, another genetic model of Down syndrome (62). In fact, EGCG has been detected in rat frontal cortex and hippocampus (60), so the effects observed in our study could be, indeed, mediated by direct action of EGCG on these structures.…”
Section: Discussionsupporting
confidence: 56%
“…This study documents serum levels of EGCG in a mouse model of DS following controlled daily dosing of 200 mg/kg pure EGCG using oral gavage, confirming our hypothesis that this dose and route of EGCG treatment produced measurable levels of EGCG in the blood in Ts65Dn and euploid mice. Other experiments with considerably less EGCG in combination with other components have also shown measurable EGCG levels in the brain and bone of TgDyrk1A mice 31 . This experimenter-controlled gavage dosing contrasts with most other studies administering EGCG in DS mouse models that typically provide EGCG (or green tea extracts containing EGCG and other catechins) in the drinking water, in which the daily dosage and pattern of EGCG (or green tea extract) consumed over the day is controlled by the drinking behavior of the subject rather than directly by the experimenter.…”
Section: Discussionmentioning
confidence: 85%
“…A nutritional supplement enriched with EGCG (94% EGCG of total catechins) showed a normalization of relevant plasma and neuronal biomarkers in mice overexpressing DYRK1A, such as BDNF and NFkB. Moreover, EGCG was able to cross the blood-brain barrier, diffusing in the brain, and has demonstrated to be safe on liver and heart function [ 50 ].…”
Section: Resultsmentioning
confidence: 99%